Evaluation of the masculinization period in the Nile tilapia spring strain employing 17α-methyltestosterone: Periodo de hormonado en tilapia. - Trejo-Quezada, Adriana; Calzada-Ruiz, Daniel; Soriano-Luis, Fredy; Valenzuela-Jimenez, Nicolas; Ramírez-Ochoa, Manuel; Moreno-de la Torre, Raúl; Alcántar-Vázquez, Juan Pablo (Ecosistemas y Recursos Agropecuarios, 2021)
An alternative to reduce the use of hormones with an immediate application to Nile tilapia commercial culture, is the precise evaluation of mas- culinization duration in domesticated strains. The main objective of this work was to evaluate the percentage of masculinization and growth obtained in Nile tilapia fed with 17α-methyltestosterone at different times during the fry period. For this, five times (0, 10, 15, 20 and 25 days) of application of the hormonal treatment were evaluated in a mixed population of Nile tilapia’s Spring strain. For each treatment, three replicates were used. Fry were stocked at a density of 0.5 L−1 in a recirculation system. Culture consisted of 30 days in 85 L acrylic aquaria and another 20 days in 1000 L exterior tanks. Squash technique was used for determination of sex. Growth was determined from wet weight and total length obtained in the biometrics. The results obtained indicated a 100% masculinization after 10 days of steroid application; but, the highest values in terms of growth rates were observed in the groups that received the steroid for the longest time. The results show that it is not necessary that the steroid is administered for 30 days to achieve a 100% masculinization in a domesticated line and that the steroid has a positive effect on the growth of the fry which persists for a few weeks after the end of the treatment.